A comparative analysis of infection in patients with malignant cancer: A clinical pharmacist consultation study. Issue 6 (November 2019) - Lin, Li; Jia, Lihua; Fu, Yali; Zhao, Ruonan; Huang, Yuan; Tang, Chuanhao; Meng, Chao; Zhao, Dazhong; Liang, Jun
Abstract: Background: Infection analysisamongst malignant cancer patients remains elusive. The objective of this study is to investigate the characteristics of both infection and anti-infection treatments in patients group with malignant cancer. Methods: We retrospectively studied the clinical data of 148 patients with malignant cancer and 171 benign patients enrolled in the pharmacist consultation from April 2015 to April 2017. Statistical analysis was performed by chi-square test to compare the classification of primary disease, sites of infection, composition of pathogenic bacteria, and the effectiveness of drug treatment. P value <0.05 was considered statistically significant. Results: A total of 102 pathogen strains were detected in the patients with malignant cancer and 129 pathogen strains were noted in the benign patient group, respectively. Statistics indicated that more abdominal infections were observed in malignant cancer patients rather than in non-cancer patients. Additionally, more pseudomonas aeruginosa infection was found in the malignant cancer patient group while more Klebsiella pneumonia infection was noted in the benign group. These findings were supported by statistical evidence. There were fewer extended-spectrum β-lactamases (ESBL) that produced Escherichia coli, which was commonly found in a gastrointestinal cancer patient group compared to patients under other types of cancer; it accounted for 51.3% of all malignant cases involved in the current study. Conclusions: Patients with malignant cancer are more likely to suffer from an infection containing pathogenic bacteria in comparison to benign patients. There have been considerable differences in the composition of pathogenic bacteria and its resistance to drugs. Overall, evaluating pathogens plays an essential role in the anti-infection treatment of patients with malignant cancer.